EFL Teachers' Perception toward the Implementation of Integrated Grammar Teaching Amidst the Global Pandemic - Dwipa, Bayu Bima (RETAIN, 2021)
This study was conducted to explore the implementation of integrated grammar teaching amidst global pandemic, then the teachers' perceptions towards integrated grammar teaching amidst global pandemic, and the challenges they faced in implementing integrated grammar teaching. This research is necessary considering the shift from offline learning into online learning give a significant alteration. Then, it also necessary to know the implementation of integrated grammar teaching in online learning since the readers could understand the implementation of grammar teaching, teachers’ perception towards it, and challenges they have face in implementing integrated grammar teaching. To determine the purpose of the study, the researcher conducted an observation using observation field notes and a semi-structured interview with all two English teachers in one of the schools in Gresik. This study used a qualitative approach with a phenomenological design. From the result of the study, it was found that the English teachers in that school implemented integrated grammar teaching well. Then, the researcher also found that all teachers considered that integrated grammar teaching is vital to be taught to the students. In addition, they also argued that the students' grammatical errors must be corrected to prevent and minimize their grammatical errors. However, the teachers faced several challenges in implementing integrated grammar teaching, for instance, the student's lack of motivation, insufficient teaching time, and reading-centered learning. Therefore, they need several supports to deal with those challenges, such as additional teaching time if the online learning is extended, the change of school syllabus, and teacher practice or training to help them improve their teaching skills. Keywords: Grammar, integrated grammar teaching, perception, teachers' perception, challenges, global pandemic